2018
DOI: 10.1093/arclin/acy038
|View full text |Cite
|
Sign up to set email alerts
|

Medication Management Performance and Associated Cognitive Correlates in Healthy Older Adults and Older Adults with aMCI

Abstract: Although these results present promising potential for the MMAA as a measure of medication management in a clinical setting, further studies need to examine the validity of the MMAA against real-world adherence measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
4
14
0
Order By: Relevance
“…Specifically, individuals with HD performed significantly worse on the total MMAA score and committed more magnitude error and total undertaking magnitude errors when compared with HA, but there was no difference in overtaking errors. Findings are consistent with prior studies examining MMAA performance in other populations, which reported that PD with MCI and older adults with aMCI performed worse than cognitively HA on the MMAA total score (Pirogovsky et al, 2014;Sumida et al, 2018). Interestingly, unlike individuals with aMCI who made significantly more overtaking and undertaking errors (Sumida et al, 2018), in the present study, individuals with HD only made significantly more undertaking magnitude errors when compared to HA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Specifically, individuals with HD performed significantly worse on the total MMAA score and committed more magnitude error and total undertaking magnitude errors when compared with HA, but there was no difference in overtaking errors. Findings are consistent with prior studies examining MMAA performance in other populations, which reported that PD with MCI and older adults with aMCI performed worse than cognitively HA on the MMAA total score (Pirogovsky et al, 2014;Sumida et al, 2018). Interestingly, unlike individuals with aMCI who made significantly more overtaking and undertaking errors (Sumida et al, 2018), in the present study, individuals with HD only made significantly more undertaking magnitude errors when compared to HA.…”
Section: Discussionsupporting
confidence: 91%
“…Findings are consistent with prior studies examining MMAA performance in other populations, which reported that PD with MCI and older adults with aMCI performed worse than cognitively HA on the MMAA total score (Pirogovsky et al, 2014;Sumida et al, 2018). Interestingly, unlike individuals with aMCI who made significantly more overtaking and undertaking errors (Sumida et al, 2018), in the present study, individuals with HD only made significantly more undertaking magnitude errors when compared to HA. Notably, until research demonstrating ecological validity for the MMAA total and process scores is completed, it is unknown whether performances on the MMAA reflect real-world medication management behaviors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Difficulty managing medications is associated with increased hospital admissions, health care costs, and mortality (34). Older adults with memory loss may rate themselves as compliant with medications even when scoring worse on a medication management test compared to healthy peers (35), indicating the early need for assistance with medications. In our study, self-reported incident difficulty with medication management was low but may have been underreported for this reason.…”
Section: Main Findingsmentioning
confidence: 99%